Student Nurses as Modern Digital Nomads: Developing Nursing Skills Competence and Confidence through Video-Based Learning - Elcokany, Nermine M.; Jaramillo, Joanne; Llaguno, Maria B. Blesilda; Seweid, Mohamed M.; Mousa, Ola (International Journal of Innovative Research in Medical Science, 2022)
The nursing staff's skills proficiency is associated with healthcare outcomes. The cornerstone of any nursing curriculum is preparing graduates to deliver safe, high-quality nursing care. The COVID-19 pandemic has, indeed, revolutionized nursing education with the adoption of innovative pedagogical strategies like blended learning. This research aims to evaluate the effectiveness of video-based instruction to determine students’ performance and confidence levels in selected nursing procedures. It also intends to investigate the factors that influencing students' nursing skills performance and confidence level. This study employed a quasi-experimental research design. This study included a total enumeration of 44 enrolled students in the nursing diploma program. The researcher divided the students into two groups by quota selection. The control group had a face-to-face teaching session in the lab. For the study group, the students recorded videos of the said procedures three times and submitted them to the faculty through the Blackboard platform. The study group scored significantly higher than the control group in different demonstration times. Specifically, the students from the study group got handwashing performance scores higher in both the first, second trials and during the final evaluation than those in the control group. This study concluded how students’ motivation and participation could improve learning outcomes. This blending of web-based training and audio-visual media provides numerous benefits. The mean self-confidence score is significantly higher in the study group than in the control group. This experience illustrates how audio-visual material can be employed to teach other nursing subjects.